Passion for Art : Ausstellung aus Anlass des 35-jährigen Bestehens der Sammlung Essl - Part II / part III. - Hoffer, Andreas; Köpf, Silvia; Maresch, Mela; Moritz, Maria Theresia; Oberhollenzer, Günther; Sibler, Urs; Sutterlüty, Anton; Zein, Sini; Essl, Karlheinz (Klosterneuburg : Essl Museum Contemporary Art Klosterneuburg Schömer-Haus Klosterneuburg, 2007)
Angeli, Eduard ; Anzinger, Siegfried ; Arcangel, Cory ; Attersee, Christian Ludwig ; Bacon, Francis ; Baechler, Donald ; Bai Yiluo ; Bailey, David A. ; Bajevic, Maja ; Balkenhol, Stephan ; Baselitz, Georg ; Baumgärtel, Tilo ; Beecroft, Vanessa ; Bell, Richard ; Beqiri, Sokol ; Bischoffshausen, Hans ; Boeckl, Herbert ; Brandl, Christian ; Brown, Cecily ; Brus, Günter ; Chapman, Dinos & Jake ; Chillida, Eduardo ; Clemente, Francesco ; Clementschitsch, Arnold ; Connelly, James ; Cragg, Tony (Anthony) ; Damisch, Gunter ; Deacon, Destiny ; diCorcia, Philip-Lorca ; Dimitrijevic, Braco ; Dine, Jim ; Djurdjevic, Bilijana ; Ebersbach, Hartwig ; Eisler, Georg ; Export, Valie ; Fahringer, Carl ; Fang Lijun ; Fischer, Johann ; Flanagan, Barry ; Flora, Paul ; Fontana, Lucio ; Francis, Sam ; Frize, Bernard ; Frohner, Adolf ; Fronius, Hans ; Gemisheva, Mariela ; Gonzenbach, Christian ; Graf, Franz ; Hahn, Christian ; Halley, Peter ; Hauser, Johann ; Hein, Jeppe ; Helnwein, Gottfried ; Henning, Anton ; Herzig, Wolfgang ; Hirst, Damien ; Hofer, Siggi ; Hollegha, Wolfgang ; Hong Hao ; Hostettler, Sylvia ; Hundertwasser ; Immendorff, Jörg ; Jahanguir ; Jorn, Asger ; Jungnickel, Ludwig Heinrich ; Jürgenssen, Birgit ; Kamlander, Franz ; Kampl, Gudrun ; Kapoor, Anish ; Karamustafa, Gülsün ; Katz, Alex ; Kiefer, Anselm ; Kippenberger, Martin ; Kirkeby, Per ; Kngwarreye, Emily Kame ; Kodritsch, Ronald ; Kogler, Peter ; Kos, Michael ; Kounellis, Jannis ; Kubin, Alfred ; Lafontaine, Marie-Jo ; Land, Peter ; Lassnig, Maria ; Lehner, Tobias ; Lezama, Daniel ; Liu Wei ; Louis, Morris ; Lüpertz, Markus ; Maciejowski, Marcin ; Maznevski, Antoni ; McCarthy, Paul ; Meese, Jonathan ; Miao, Xiaochun ; Mikl, Josef ; Mosbacher, Alois ; Mühl, Otto ; Muñoz, Juan ; Muntean & Rosenblum ; etc.
geboortejaar en - plaats p. 542-557
2 volumes : part II, part III
Engels
Passion for Art : 35th anniversary of the Essl Collection 1972-2007, Essl Museum Contemporary Art Klosterneuburg, 15.03 - 26.08.2007
boek